2015
DOI: 10.1175/waf-d-14-00141.1
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis on the Dependence of Tropical Cyclone Intensification Rate on the Storm Intensity and Size in the North Atlantic

Abstract: The dependence of tropical cyclone (TC) intensification rate IR on storm intensity and size was statistically analyzed for North Atlantic TCs during 1988-2012. The results show that IR is positively (negatively) correlated with storm intensity (the maximum sustained near-surface wind speed V max ) when V max is below (above) 70-80 knots (kt; 1 kt 5 0.51 m s 21 ), and negatively correlated with storm size in terms of the radius of maximum wind (RMW), the average radius of gale-force wind (AR34), and the outer-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 26 publications
(32 reference statements)
8
51
1
Order By: Relevance
“…However, combining these statistics with the RMW sizes observed in Figure 2.3 demonstrates that the average RMW of an IN hurricane or major hurricane is smallest when compared to SS and WK hurricanes or major hurricanes, respectively. This is in general agreement with results presented by Xu and Wang (2015) who showed that intensification rates were negatively correlated with RMW size. Although intensification rates were not examined in this study beyond the threshold criteria used to bin the data, the results suggest that TCs with a smaller RMW favor intensification at both hurricane and major hurricane intensity.…”
Section: Large Scale Characteristicssupporting
confidence: 93%
“…However, combining these statistics with the RMW sizes observed in Figure 2.3 demonstrates that the average RMW of an IN hurricane or major hurricane is smallest when compared to SS and WK hurricanes or major hurricanes, respectively. This is in general agreement with results presented by Xu and Wang (2015) who showed that intensification rates were negatively correlated with RMW size. Although intensification rates were not examined in this study beyond the threshold criteria used to bin the data, the results suggest that TCs with a smaller RMW favor intensification at both hurricane and major hurricane intensity.…”
Section: Large Scale Characteristicssupporting
confidence: 93%
“…During the 48‐hr period of landing, the heavy rain and moderate rain areas decrease gradually all the time for TY and TS grades but remain unchanged for TDs, although the storm intensities are all weakened due to the cutoff of moisture transport (not shown), suggesting that some factors other than storm intensity may play important roles in the rainfall coverage for these not very strong TCs. Previous results revealed a weak positive correlation between TC size (represented by radius of maximum wind or precipitation circles) and TC intensity (e.g., Guo & Tan, ; Merrill, ; Wu et al, ; Xu & Wang, ). Our result enriches their finding and further reveals that while TC intensity likely affects its rainfall intensity (Figure ) and rainfall coverage (Figure ), especially when the storm is over the ocean, some processes associated with landing may have even broader impacts on the rainfall distribution of the TC.…”
Section: General Characteristics Of Rainfall Distribution For Landfalmentioning
confidence: 92%
“…Irish et al () stated that for a given TC intensity, the size of storm can account for the variation of storm surge up to 30%. However, there is a weak correlation between TC intensity and TC size (e.g., Merrill, ), and their relationship is nonlinear according to recent research (e.g., Wu et al, ; Xu & Wang, ). Hill and Lackmann () presented that the intensity and coverage of precipitation occurring outside the TC core are sensitive to environmental relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the cold wake size can thus provide another measurement of TC size and broaden our understanding of their impacts on the climate. TC size, in addition to TC intensity, has been found to be vital to TC intensification and TC‐induced damage in recent years (Carrasco et al, ; Chavas et al, ; Guo & Tan, ; Knutson et al, ; Lin & Chavas, ; Xu & Wang, ). Almost all current size metrics of TCs, however, are derived from atmospheric features, such as wind, sea level pressure, rainfall, and clouds (Chavas et al, ; Chavas & Emanuel, ; Kimball & Mulekar, ; Knaff et al, ; Lin et al, ; Merrill, ).…”
Section: Introductionmentioning
confidence: 99%